Perancangan Sistem Informasi Pengenalan Tempat Wisata Di Aceh - Taufiq Taufiq; Munar Munar (Jurnal Tika, 2021)
This Information System aims to promote tourist attractions in Aceh Province. The information system is designed to be web-based whose media has elements of text, images, animations and even sound. These elements make this media interesting. In addition, this web-based information system has become a medium that has quite complete information for tourists that can be viewed any time needed. The design of this system cannot be separated from the aspects of design and technology in the manufacturing process. Like other information media, the success of this media is also determined by the success in delivering information. The research method is collecting data through literature studies, interviews, and observations, as well as analyzing software requirements, building databases with MySQL, designing interfaces using Photoshop and PHP, conducting program testing as the final stage in making a web-based tourism information system. In the Design of Web-Based Tourism Information System, there is a procedural process carried out to collect data. The data collection used is observation related to tourism objects in Aceh Province. In addition to observations, unstructured interviews were also carried out, where interviews were conducted freely, not using interview guidelines systematically, besides that the data in this design were data on tourism obtained from books, brochures, and browsing on the internet. The results of the design are in the form of a web-based tourism information system which is expected to be a medium that can promote tourism objects in Aceh